The Contribution of Skilled Nursing Facilities to Hospitals’ Readmission Rate - Rahman, Momotazur; McHugh, John; Gozalo, Pedro L.; Ackerly, Dana Clay; Mor, Vincent (Health services research, 2017)
Objective To examine the relative influence of hospital and skilled nursing facilities (SNFs) on 30‐day rehospitalization. Data Sources/Settings Elderly Medicare beneficiaries newly admitted to a SNF following hospitalization. Study Design We ranked hospitals and SNFs into quartiles based on previous years’ adjusted rehospitalization rates (ARRs) and examined how rehospitalizations from a given hospital vary depending upon the admitting SNF ARR quartile. We examined whether the availability of SNFs with low rehospitalization rates influenced hospitals’ SNF readmission rates and whether changes in a hospital's ARR over 3 years is associated with changes in the SNFs to which they discharge. Principal Findings Hospital readmission rates from SNFs varied 5 percentage points between patients discharged to SNFs in the lowest and the highest rehospitalization quartiles. Low rehospitalization rate hospitals sent a larger fraction of their patients to the lowest rehospitalization SNFs available in the area. A 10 percent increase in hospital's share of discharges to the lowest rehospitalization quartile SNFs is associated with a 1 percentage point reduction in hospital's ARR. Conclusions The SNF rehospitalization rate has greater influence on patients’ risk of rehospitalization than the discharging hospital. Identifying high‐performing SNFs may be a powerful strategy for hospitals to reduce rehospitalizations.